Teacher professional development during the sanitary contingency from the principals’ perspective - Rivera Ceseña, Karen Patricia; Cordero Arroyo, Graciela; Reyes-Angona, Sergio (IE Revista de Investigación Educativa de la REDIECH, 2022)
The educational field is one of the most affected by COVID-19. Teachers have had to adapt to develop their classes in completely different environments from the usual ones. Despite the abundant investigation of the new educational conditions, a little explored aspect has been the offer of training received by teachers in this context. The goal of this article is to analyze the perception and opinion of Mexican primary school administrators regarding the offer of continuous training to teachers during the months of health contingency, and the way in which they have attended to said offer or promoted other actions. The research is exploratory and has a qualitative approach. Semi-structured interviews were applied to seven directors of elementary education from different regions of the country, and their content was analyzed qualitatively. The main finding is the multiplication of the self-administered training offer and the parallel impulse given by teaching groups to self-training and peer training initiatives. It concludes on the necessity to combine two components for teacher training: 1) the self-administered training offer, and 2) the accompaniment of teachers in their training processes, with special attention to their professional practice.